THE IMPORTANCE OF TOURISM ZONES IN THE DEVELOPMENT OF THE TOURISM SECTOR IN KASHKADARYA REGION - Islomov Furkat , Usmon ugli (THE INNOVATION ECONOMY, 2025)
This article reflects the reforms being implemented to develop the tourism sector in Kashkadarya region, the development of tourism zones, and their role in the economy, the flow of foreign tourists, and the opportunities created for tourists. Additionally, it discusses in detail the measures that need to be taken to increase the share of the tourism sector in the region's economy and attract more foreign tourists in the future.